If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 4 + -5x Reorder the terms: 5 + 3x = 4 + -5x Solving 5 + 3x = 4 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 5 + 3x + 5x = 4 + -5x + 5x Combine like terms: 3x + 5x = 8x 5 + 8x = 4 + -5x + 5x Combine like terms: -5x + 5x = 0 5 + 8x = 4 + 0 5 + 8x = 4 Add '-5' to each side of the equation. 5 + -5 + 8x = 4 + -5 Combine like terms: 5 + -5 = 0 0 + 8x = 4 + -5 8x = 4 + -5 Combine like terms: 4 + -5 = -1 8x = -1 Divide each side by '8'. x = -0.125 Simplifying x = -0.125
| -24c=36c | | 5x^2-16x+15x=4x-5 | | 1x+6x-7-6=12x+15 | | 2(3-x)=5(4x-1) | | 8x-2=11x+7 | | .5(5x+4)-.33(x+7)=4 | | 81+8=6+5 | | 3x+15=33 | | 8-81=5-6 | | 3(y-8)=4(2y+9) | | 2x=7+-43-8x | | 9-p=4p-11 | | 2x-10=7x-11 | | 6a-16+6a-15+6a+7=48 | | -4x+6+x=-2x+x-10 | | -3x-8+x=-4x+-10 | | c/4=16 | | x-(-12)=2 | | 2(x+10)-5(2-x)+3=0 | | 81-4x^2=0 | | x-(-8)=-28 | | (x^2-11+19-x)(-10)= | | (3x-5)+(3x+5)+x=180 | | 4m^3-9=23 | | x-(-1)=50 | | 3.2b+8=20 | | 2+6x-3-3x=0 | | 22=4(5y-2) | | x-(-5)=10 | | x+(x+5)+x+(x+5)=26 | | 19=17-2x | | 9-5t=3t+18 |